2016
DOI: 10.3390/su8040300
|View full text |Cite
|
Sign up to set email alerts
|

Women on Boards and Corporate Social Responsibility

Abstract: A growing body of research suggests that having more women in the boardroom leads to better corporate social responsibility (CSR) performance. However, much of this work views the CSR-enhancing effect of women directors as largely driven by their moral orientations and rarely considers other underlying mechanisms. Moreover, less explored are the firm-specific conditions under which such CSR-promoting roles of female directors might be performed more (or less) effectively. In this paper, we seek to bridge this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
0
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(120 citation statements)
references
References 51 publications
(103 reference statements)
6
95
0
8
Order By: Relevance
“…Williams [67] showed that an increasing number of women members on the boards is positively related to the firm's level of charitable giving to the arts and community. Hyun et al [68] argue that independent female directors in comparison to males might take CSR issues more seriously because of their stronger moral orientations and reputational reasons to do so. According to their research results, the number of independent female directors is positively associated with a firm's CSR ratings.…”
Section: Women On the Boardmentioning
confidence: 99%
“…Williams [67] showed that an increasing number of women members on the boards is positively related to the firm's level of charitable giving to the arts and community. Hyun et al [68] argue that independent female directors in comparison to males might take CSR issues more seriously because of their stronger moral orientations and reputational reasons to do so. According to their research results, the number of independent female directors is positively associated with a firm's CSR ratings.…”
Section: Women On the Boardmentioning
confidence: 99%
“…For instance, studies showed that certain psychological and socio-economic traits of high-ranking corporate officers tend to affect the CSR performance of their firms. This stream of work notes that the level of CSR efforts by firms is partly determined by the moral orientations of the individuals in influential positions [18][19][20]. More interestingly, some researchers suggested that the desires of the upper-echelon members of firms for more public attention, a better reputation, and higher labor market value are also important drivers behind their firms' pursuit of CSR initiatives [20,21].…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Having reviewed the literature on the relationship between board diversity and corporate social responsibility, Rao and Tilt [23] highlight the importance of linking the gender diversity on the board to the decision-making process of corporate social responsibility. Hyun et al [6] considered the inherent mechanism of female directors and obtained positive correlation between the number of female independent directors and corporate social responsibility, which is a further promotion of prio studies. Taking the sample of 91 listed companies in France in 2001-2011, Nekhili et al [24] find that board diversity has an impact on corporate social responsibility.…”
Section: Introductionmentioning
confidence: 99%
“…The motivation of enterprises to actively undertake social responsibility and carry out environmental investment activities is obvious. Having good corporate social responsibility helps to improve corporate transparency and reduce the information asymmetry between business and stakeholders [5] and to improve long-term corporate value [6]. According to the quaternity indicator system in Research Report on Corporate Social Responsibility of China, social responsibility includes four aspects: management responsibility, market responsibility, public welfare responsibility and environmental responsibility.…”
Section: Introductionmentioning
confidence: 99%